Supporting Nuclear Non-Proliferation and Disarmament - Rob van Riet, Alyn Ware (2012)
This Handbook has been produced to assist parliaments and parliamentarians in implementing those nuclear non-proliferation and disarmament goals. It highlights a range of existing good policies and practices aimed at furthering nuclear disarmament, curbing nuclear proliferation, or safeguarding nuclear security, and explores what parliamentarians can further do to fashion the legislative agendas needed to advance these goals.